Effect of Anti-Tobacco Audiovisual Messages on Knowledge and Attitude towards Tobacco Use in North India - Jagdish Kaur; Jugal Kishore; Monika Kumar (Wolters Kluwer Medknow Publications, 2012)
Context: Tobacco use is one of the leading preventable causes of death globally. Mass media plays a significant role in initiation as well as in control of tobacco use. Aims: To assess the effect of viewing anti-tobacco audiovisual messages on knowledge and attitudinal change towards tobacco use. Settings and Design: Interventional community-based study. Materials and Methods: A total of 1999 cinema attendees (age 10 years and above), irrespective of their smoking or tobacco using status, were selected from four cinema halls (two urban, one semi-urban, and one rural site). In pre-exposure phase 1000 subjects and in post-exposure phase 999 subjects were interviewed using a pre-tested questionnaire. After collecting baseline information, the other days were chosen for screening the audiovisual spots that were shown twice per show. After the show, subjects were interviewed to assess its effect. Statistical Analysis Used: Proportions of two independent groups were compared and statistically significance using chi-square test was accepted if error was less than 0.05%. Results: Overall 784 (39.2%) subjects were tobacco users, 52.6% were non-tobacco users and 8.2% were former tobacco users. Important factors for initiation of tobacco use were peer pressure (62%), imitating elders (53.4%) and imitating celebrity (63.5%). Tobacco users were significantly less likely than non-tobacco users to recall watching the spots during movie (72.1% vs. 79.1%). Anti-tobacco advertisement gave inspiration to 37% of subjects not to use tobacco. The celebrity in advertisement influenced the people's attention. There was significant improvement in knowledge and attitudes towards anti-tobacco legal and public health measures in post exposure group. Conclusions: The anti-tobacco advertisements have been found to be effective in enhancing knowledge as well as in transforming to positive attitude of the people about tobacco use.